Kebijakan Hutang Melalui Free Cash Flow, Kepemilikan Manajerial dan Kebijakan Deviden - Hasmaynelis Fitri; Depi Gusti Apriyanti; L Lusiana; Ramdani Bayu Putra; Sitti Rizki Mulyani (Jurnal Informatika Ekonomi Bisnis, 2022)
This study aims to determine the relationship between the influence of Managerial Ownership, Dividend Policy and Investment Opportunity Set on debt policy with Free Cash Flow as a Moderating Variable in Manufacturing Companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2016-2020, totaling 195 companies. The sample of this research is 66 companies in 5 years, so the total data obtained is 330 using purposive sampling technique. The data in this study is secondary data in the form of annual data obtained from the official website of the Indonesia Stock Exchange, the official website of the company concerned. The data analysis method used in this research is descriptive statistical test, classical assumption test, panel data regression analysis and hypothesis testing using Eviews 9. The results show that a) Managerial Ownership has a positive and significant effect on debt policy, b) Dividend Policy has no effect on debt policy c) Investment Opportunity Set has no effect on debt policy d) Free cash flow is able to strengthen the influence of managerial ownership on debt policy e) Free cash flow is not able to strengthen the effect of dividend policy on debt policy. f) Free cash flow is not able to strengthen the effect of investment opportunity set on debt policy.